Analysis Cost of Fund, Cost of Loanable Fund, and Overhead Cost on Mudharabah Profit Sharing at Islamic Commercial Banks - Apriliyani, Lisa; Yahya, Alvin (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: The operations of Islamic banks are based on the mudharabah profit-sharing system, which governs both fund collection and distribution. This system often leads to higher operational costs compared to conventional banks. The study aims to analyze the mudharabah profit-sharing ratio by examining the Cost of Funds (COF), Cost of Loanable Funds (COLF), and Overhead Costs (OHC). Research Methods: This study uses secondary data from published financial reports, with 40 samples taken from annual reports for the 2020–2023 period. The data are analyzed using descriptive analysis, classical assumption tests, and multiple linear regression to measure the effect of each variable. Results: The results show that COF has a significant negative effect on mudharabah profit sharing, COLF has no significant effect, while OHC has a significant positive effect. Conclusion: Efficient management of funding and overhead costs is essential to enhance the profitability of mudharabah-based Islamic banks. Meanwhile, the cost of loanable funds has no significant role in determining the profit-sharing ratio.